2016
DOI: 10.3390/molecules22010024
|View full text |Cite
|
Sign up to set email alerts
|

Literature Survey and Further Studies on the 3-Alkylation of N-Unprotected 3-Monosubstituted Oxindoles. Practical Synthesis of N-Unprotected 3,3-Disubstituted Oxindoles and Subsequent Transformations on the Aromatic Ring

Abstract: The paper provides a comprehensive review of the base-catalysed C3-alkylation of N-unprotected-3-monosubstituted oxindoles. Based on a few, non-systematic studies described in the literature using butyllithium as the deprotonating agent, an optimized method has now been elaborated, via the corresponding lithium salt, for the selective C3-alkylation of this family of compounds. The optimal excess of butyllithium and alkylating agent, and the role of the halogen atom in the latter (alkyl bromides vs. iodides) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Deprotonation with BuLi leading to the formation of the corresponding dianions was performed at −78 °C in each case, although with different amounts of BuLi (2.4–3.0 eq.). Then, contrary to our earlier observations with 3-monoalkyloxindoles ( 9 ) where MeI was also added at −78 °C [ 17 ], for 1,3-diazaoxindoles 24a – c we found that addition of MeI had to be carried out at −20 °C so that starting materials 24a – c are fully consumed. Finally, the reaction mixture was allowed to warm to ambient temperature.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Deprotonation with BuLi leading to the formation of the corresponding dianions was performed at −78 °C in each case, although with different amounts of BuLi (2.4–3.0 eq.). Then, contrary to our earlier observations with 3-monoalkyloxindoles ( 9 ) where MeI was also added at −78 °C [ 17 ], for 1,3-diazaoxindoles 24a – c we found that addition of MeI had to be carried out at −20 °C so that starting materials 24a – c are fully consumed. Finally, the reaction mixture was allowed to warm to ambient temperature.…”
Section: Resultscontrasting
confidence: 99%
“…As demonstrated by the reactions carried out using NaOH at our laboratory and by the procedures described in the literature using sodium, potassium or cesium bases for the deprotonation of 1,3-diazaoxindoles, selective alkylation at the C (5) position could not be achieved. Therefore, we continued our efforts by applying BuLi as the base in the alkylation reactions, which proved to be the optimal base in the analogous regioselective C (3)-alkylation reactions of N -unprotected oxindoles, particularly for the introduction of a second substituent into the carbonyl-adjacent C (3) position of N -unprotected 3-monoalkyloxindoles 9 ( Scheme 2 ) [ 17 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing synthetic methods mainly rely on the use of preexisting oxindole cores to form 3,3′-disubstituted oxindoles via a typical functionalization step. 11 In addition, cyclization reactions represent widely used strategies for the construction of oxindole motifs. However, these methods inherently require an ortho -functionalized aryl group and 2-substituted activated anilides ( Fig.…”
Section: Introductionmentioning
confidence: 99%